Magill's cinema annual 2015 a survey of the films of 2014 - Tallerico, Brian; Gale Group (Farmington Hills, Mich. Gale, Cengage Learning, 2015)
Offers an in-depth retrospective of significant domestic and foreign films released in the United States during the preceding year. Distinguishing features include its extensive credits, awards and nominations, MPAA ratings, thorough indexes, and its exhaustive critical reviews with author bylines.
Preface -- Introduction -- Contributing reviewers -- User's guide -- The films of 2014 -- List of awards -- Obituaries -- Selected film books of 2014 -- Director index -- Screenwriter index -- Cinematographer index -- Editor index -- Art director index -- Music director index -- Performer index -- Subject index -- Title index.
Includes indexes.
"ISSN 0739-2141."
"A VideoHound Reference."
Keywords: Motion pictures -- Periodicals